2017
DOI: 10.1080/13683500.2017.1367367
|View full text |Cite
|
Sign up to set email alerts
|

A review of eye-tracking research in tourism

Abstract: This study provides a review of eye-tracking as a technique for measurement of attention. The review discusses its theoretical basis, advantages and disadvantages, data collection procedures, analysis methods and application in tourism and hospitality. Areas for further research in tourism and hospitality are provided based on a systematic review of tourism research using eye-tracking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(141 citation statements)
references
References 102 publications
(136 reference statements)
3
135
0
3
Order By: Relevance
“…These were classified in order of importance by the number of text blocks associated with each theme (i.e. hits) (Scott, Zhang, Le, & Moyle, 2017 hits) and fantasy (5 hits). Three important themes are further analysed in this paper: how imagery processing has been studied (i.e.…”
Section: Content Analysis By Leximancermentioning
confidence: 99%
“…These were classified in order of importance by the number of text blocks associated with each theme (i.e. hits) (Scott, Zhang, Le, & Moyle, 2017 hits) and fantasy (5 hits). Three important themes are further analysed in this paper: how imagery processing has been studied (i.e.…”
Section: Content Analysis By Leximancermentioning
confidence: 99%
“…Eye tracking is a valuable tool for measuring attention in tourism (Scott, Zhang, Le, & Moyle, 2017) and hospitality . Eye tracking has been used to investigate the effectiveness of tourism advertisements (Scott, Green, & Fairley, 2016;Wang & Sparks, 2014); to design tourism experiences (Li, Scott & Walters, 2015) such as hotel pictures (Wang, Tsai & Tang, 2018); to optimize restaurant menus (Yang, 2012), and to assess the usability of websites (Marchiori & Cantoni, 2015;Green, Murray, & Warner, 2011;Pan et al, 2004;Pan, Zhang, & Smith, 2011), including accommodation websites (Hao, Tang, Yu, & Law, 2015;Pan, Zhang, & Law, 2013).…”
Section: Measuring Attention With Eye Trackingmentioning
confidence: 99%
“…The analysis showed that the sample size and characteristics of this study were sufficient for hypothesis testing. In addition, Scott et al [48] reviewed eye-tracking research in the tourism field and found that eye-tracking research designs have been used with between 12 and 63 participants. The present study's sample (113 participants) was larger than the sample (between 12 and 63 participants) used in previous studies.…”
Section: Samplementioning
confidence: 99%